Analyzing the impact of knowledge management and decision making levels of supply chain on organizational performance in Thai manufacturers - Anurak Sawangwong (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The purpose of this study is to analyze the impact of Knowledge Management (KM) and Decision Making Levels of Supply Chain (DMSC) on Organizational Performance (OP) from the perspective of Thai Manufacturers. This study is divided into three main stages namely: the analyses of the interrelationships of all KM processes, the impact analyzes of KM on DMSC and the impact analyses of DMSC on OP. The conceptual framework was designed based on the concept of the KM, DMSC, and OP via literature review. This research was surveyed by collecting data from 255 manufacturing companies with questionnaire and data analysis which was conducted by using covariance-based structural equation modelling (CBSEM). This study provides empirical evidence and confirms the results of the concepts of the interrelationships between the KM processes. Overall, KM processes (knowledge acquisition, distribution, application and retention) are positively related to DMSC (strategic level of supply chain, tactical and operational). The relationships between the two level of DMSC (tactical level of supply chain and operational) are positively related to OP. To the best of author’s knowledge, very few research has been conducted to examine the relationship between the KM and DMSC, especially on the aspects of DMSC. Finally, this study can be used as a guideline for practitioners at each level of the supply chain decision making, and to increase performances of the organization.